Synthesis and bioactivities of substituted quinolines and nanogels - Shi, Aibin (Kansas State University, 2009)
The first section of this thesis deals with the synthesis of substituted quinolines and its bioactivities against gap junction. Cancer cells are characterized by down regulated or altered gap junction intercellular communication (GJIC) activities; enhancement of GJIC would provide a pathway for the delivery of anticancer drugs. Our computational studies using Autodock found binding interactions between gap junction channels and substituted quionlines (code name PQs). Thus, a serial of PQ compounds were synthesized and their activities against GJIC were tested. Among these synthesized PQs, 6-Methoxy-8-[(3-aminopropyl) amino]-4- methyl-5-(3-trifluoromethyl- phenyloxy)quinoline (PQ1) can specifically enhance GJIC activity of T47D cells without affecting the normal MECs. The PQ1 induced apoptosis can spread throughout the gap juctions, consequently cause the decrease of cell viability and colony growth. PQ1 can attenuate tumor growth of xenograft tumors in Nu/Nu mice. Compound 7 (code PQ11) which has an IC50 of 15.6nM against T47D cancer cell, is a promising candidate for further pharmacological studies. The second section of this thesis deals with the synthesis and anticancer bioactivities of PEG-PEI based nanogels. Nanogels were synthesized, encapsulated with anticancer drugs, and loaded to stem cells. Stem cells can target at the cancer cell and release the nanogel and anticancer drug to kill the cancer cell. The nontoxic PEG-PEI nanogel which can be loaded to stem cells was successfully synthesized by doubly treatment of PEI with activated PEG. Based on this nontoxic nanogel, two other types of nanogels were synthesized. In one type of nanogel, an anticancer drug, SN38 was modified and attached to the nontoxic nanogel via a tetra-peptide linker. This tetra peptide can be recognized and cut by legumain, a protein that highly over expressed in many tumors, to release the drug to tumors. In the other type of nanogel, straptavidin was attached to the nanogel which can bind to biotin and recognized by tumor. The result indicated this type of nanogel can be loaded to stem cells within 15 minutes.
Keywords: quinoline; nanogel; anticancer; Chemistry, Organic (0490)